학교운동부지도자의 직업적 고충과 대응에 관한 연구 - 유주영; Ju-young Ryou; 이옥선; Ok-seon Lee (Ch'eyuk kwahak yŏn'gu, 2020)
[목적] 본 연구의 목적은 학교운동부지도자의 직업적 고충을 중층(관계-제도)의 관점에서 이해하고, 대응의 성질을 분석함으로써, 향후 인권·친화적 학교운동부 시스템 정착을 위한 시사점을 제공하는 데 있다. [방법] 이를 위해 초, 중, 고 학교운동부지도자(n=5, 평균경력 19.2년)를 참여자로 선정하였다. 연구자료는 반-구조화된 면담으로 수집되었다. 수집된 자료는 귀납적으로 분석되었다(Patton, 2015). [결과] 첫째, 참여자들은 학교운동부 조직 내외의 이해당사자들의 역할기대에 지쳐있었다. 둘째, 운동부 관련 제도 및 정책인 학습권 보장제, 주 52시간 근로제, 인권 보장제는 지도자들의 공식적, 비공식적 역할수행에 어려움을 가중시켰다. 셋째, 이해당사자들의 관계적 요구와 정부기관의 제도적 이상의 불협화음은 참여자들로 하여금 반제도적, 비윤리적, 비교육적 자충수를 택하도록 종용하였다. [결론] 연구결과를 바탕으로 ‘인권 친화적 학교운동부 문화의 토착화를 위해 정부, 학계, 사회전반이 운동부지도자를 ‘혁신의 대상’으로 설정하기보다, 함께 문제를 풀어갈 ‘혁신의 주체’로 재인식해야 함을 제언하였다. 이러한 결론은 이해당사자들의 요구와 관련 정책의 간극을 좁히는데 유효한 시사점을 제공할 것으로 기대된다. [Purpose] The purpose of this study was to understand student athletes coaches’ occupational challenges from the dual perspectives(social relationship-political system), to analyze the nature of the coping strategies for the challenges, and to provide implications for building a human rights-friendly student athletes club culture. [Methods] Five coaches(n=5, average career length= 19.2 years) were selected through purposeful sampling. Data were collected by semi-structured interviews with participants. The collected data were inductively analyzed(Patton, 2015). [Results] First, participants struggled with informal roles demanded by the interested parties(principals, athletic directors, parents, and university coaches). Second, the system for protecting student athletes’ learning rights, the 52-hour work system and the human rights system added difficulties to the coaches’ work environment. Third, the disharmony between interested parties’ demands and government agencies’ institutional ideals pushed participants to choose anti-institutional, un-ethical, un-educational coping strategies. [Conclusion] The findings suggest that the government, academia and the community should empower coaches as ‘the subject of reform’ who can solve the problem together rather than regarding them as ‘the object of reform.’ Furthermore, this conclusion is expected to provide implications to alleviate disharmony between interest parties’ demands and government agencies’ systems.’